Household Debt and Fiscal Multipliers. (14th September 2015) - Andrés, J.; Boscá, J. E.; Ferri, J.
Abstract : We study the size of government spending multipliers in a general equilibrium model with search and matching frictions in which we allow for different levels of household indebtedness. The main results are: (a) the presence of impatient households and private debt helps to generate government spending multipliers greater than 1; (b) as financial conditions worsen, the size of the government spending multiplier falls; (c) conversely, employment, vacancies and unemployment multipliers are larger in a credit crunch; (d) the model explains the observed pattern of responses of labour market variables, housing prices and private debt to a fiscal shock reasonably well.